Legal Liability For Losses Of Third Parties In The Agreement To Transfer Property Rights With An Absolute Power Of Attorney - Finni Rahmawati (Universitas Islam Negeri Antasari Banjarmasin, 2021)
Abstract: An agreement to transfer title to land based on absolute power is prohibited by law. The prohibition of absolute power is regulated in Instruction of the Minister of Home Affairs number 14 of 1982 concerning the Prohibition of Using Absolute Power for Transfer of Rights to Land, and Government Regulation No. 24 of 1997 Article 39 paragraph (1) letter d concerning land registration. However, the reality is that there is still a land sale and purchase agreement using an absolute power of attorney, causing losses to other parties. The problem is how is the legal responsibility of the seller and the notary against the loss of a third party due to the use of absolute power of attorney in the agreement to transfer title to land. This study aims to determine the legal liability of the seller and the notary against the losses of third parties due to the use of absolute power of attorney in the agreement to transfer ownership of land rights. The method used in this study is a normative juridical method using a statuate approach and case approach. The Study found that the seller's responsibility was based on Article 1365 of the Civil Code, namely by providing compensation for the value of the sale value of the land minus the owner's debt without involving a third party with good faith. And the accountability of the notary is contained in Law Number 30 of 2014 Article 84 concerning the Position of Notary Public and Government Regulation Number 24 of 1997 Article 62 concerning Land Registration which explains the sanctions for notaries. In this case it relates to the loss of a third party in good faith.Keywords: Absolute Power, CompensationAbstrak: Perjanjian pengalihan hak milik atas tanah yang didasarkan pada kuasa mutlak merupakan sesuatu yang dilarang oleh hukum. Pelarangan kuasa mutlak diatur dalam Instruksi Menteri Dalam Negeri nomor 14 Tahun 1982 tentang Larangan Penggunaan Kuasa Mutlak Sebagai Pemindahan Hak Atas Tanah, dan Peraturan Pemerintah No. 24 Tahun 1997 Pasal 39 ayat (1) huruf d tentang pendaftaran tanah. Namun realitas yang terjadi masih terdapatnya suatu perjanjian jual beli tanah menggunakan surat kuasa mutlak sehingga menyebabkan kerugian bagi pihak lain. Permasalahannya adalah bagaimanakah pertanggungjawaban hukum pihak penjual dan notaris terhadap kerugian pihak ketiga akibat penggunaan surat kuasa mutlak dalam perjanjian pengalihan hak milik atas tanah. Penelitian ini bertujuan untuk mengetahui pertanggungjawaban hukum pihak penjual dan notaris terhadap kerugian pihak ketiga akibat penggunaan surat kuasa mutlak dalam perjanjian pengalihan hak milik atas tanah. Metode yang digunakan dalam penelitian ini yaitu metode yuridis normatif dengan menggunakan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian ditemukan bahwa pertanggungjawaban pihak penjual yakni berdasarkan Pasal 1365 KUHPerdata yaitu dengan memberikan ganti kerugian seharga nilai penjualan tanah dikurangi hutang pemilik tanpa melibatkan pihak ketiga yang beritikad baik. dan pertanggungjawaban pihak notaris yaitu terdapat dalam UU Nomor 30 Tahun 2014 Pasal 84 tentang Jabatan Notaris dan Peraturan Pemerintah Nomor 24 Tahun 1997 Pasal 62 tentang Pendaftaran Tanah yang menjelaskan sanksi bagi notaris. Dalam hal ini berhubungan dengan kerugian pihak ketiga yang beritikad baik.Kata Kunci: Kuasa Mutlak, Ganti Kerugian